2011
DOI: 10.1063/1.3574395
|View full text |Cite
|
Sign up to set email alerts
|

Coherent vibrational energy transfer along a peptide helix

Abstract: To measure the transport of vibrational energy along a peptide helix, Hamm and co-workers [J. Phys. Chem. B 112, 9091 (2008)] performed time-resolved vibrational experiments, which showed that the energy transport rate increases by at least a factor of 4, when a localized C=O mode of the peptide instead of an attached chromophore is excited. This finding raises the question if coherent excitonic energy transfer between the C=O modes may be of importance for the overall energy transport in peptides. With this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…For instance, recent experiments revealed that the coherent nature of the exciton may explain the remarkable efficiency of light-harvesting complexes [21,22]. Similarly, in a peptide helix, it has been shown that when a localized amide-I mode is selectively excited, the energy transport rate drastically increases [23] suggesting that a coherent energy flow takes place * Electronic address: vincent.pouthier@univ-fcomte.fr between amide-I modes [24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent experiments revealed that the coherent nature of the exciton may explain the remarkable efficiency of light-harvesting complexes [21,22]. Similarly, in a peptide helix, it has been shown that when a localized amide-I mode is selectively excited, the energy transport rate drastically increases [23] suggesting that a coherent energy flow takes place * Electronic address: vincent.pouthier@univ-fcomte.fr between amide-I modes [24].…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients provide the instantaneous populations of the sites and the instantaneous interstate coherences. 24 To compute observables, the statistical density matrix must be computed by averaging the instantaneous values c * m (t)c n (t) over trajectories describing the ensemble. Such a procedure yields the statistical density matrix…”
Section: The Vibrational Dynamicsmentioning
confidence: 99%
“…From a theoretical point of view, the intramolecular vibrational energy flow in biomolecules has also received a great deal of attention 2, 28 through different approaches including harmonic theories, 8,26,[29][30][31][32][33] molecular dynamics (MD) simulations, 28,[34][35][36][37][38][39][40][41][42][43][44][45][46] coarse-grained models, 33,47 and quantum methods. 21,[48][49][50][51][52][53] Despite this diversity of theoretical treatments, comparison between experimental and theoretical studies is still unsatisfactory because it faces the major difficulty that whereas experiments provide information on the energy transport spectroscopically from the vibrational modes which are active in the technique employed, most of the theoretical treatments discuss the energy flow in terms of residuebased models which, although shown to be quite useful in describing the spatial evolution of the energy, 38,39,41,44 are not well suited for direct comparison with observed data since the residues are not the experimentally active units.…”
Section: Introductionmentioning
confidence: 99%